Keefektifan Model Pembelajaran Student Teams Achievement Devision (STAD) Berbantuan Media Puzzle untuk Meningkatkan Pemahaman Konsep IPA pada Siswa Kelas 4 SD Negeri 1 Prigi - Arumsari, Desy Retno; Suryani, Ela (Universitas PGRI Semarang, 2023)
The purpose of this study was to determine the effectiveness of using the Student Teams Ahievement Division (STAD) learning model assisted by Puzzle media on understanding the concept of science in class IV students at SDN I Prigi. This study uses a quantitative approach with a research design that is a quasi-experimental design in the form of a non-equivalent control group design. Samples were taken by purposive sampling technique. SDN 1 Prigi as the experimental class and class IV SDN 3 Prigi as the control class. Data collection techniques using observation techniques, tests, and documentation. The data analysis technique used is the Normality Test, Homogeneity Test, Independent Sample T-Test, Simple Linear Regression Test, Paired Sample T-Test. The results of this study indicate: (1) There are differences in the student teams achievement division (STAD) learning model assisted by media puzzles in terms of understanding science concepts in experimental class students and the student teams achievement division (STAD) learning model without puzzle media, this is evidenced by a significant level 0.000 which is 0.05 using an independent sample t-test. (2) There is an influence of the student teams achievement division (STAD) learning model assisted by media puzzles on increasing students' understanding of science concepts, this is evidenced by a significant level of 0.002, which is 0.05 using a simple linear regression test. (3) The student teams achievement division (STAD) learning model assisted by puzzle media can improve students' understanding of science concepts, this is evidenced by a significant level of 0.000, which is 0.05 using a paired sample t-test. Based on this study it can be concluded that there are differences, influences, and increased understanding of the concept of science in the use of the student teams achievement division (STAD) model assisted by media puzzles for students at SDN 1 Prigi.